1998
DOI: 10.1084/jem.188.11.2007
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Exposure to a Self-Peptide–Immunoglobulin Chimera Circumvents the Use of Adjuvant and Confers Resistance to Autoimmune Disease by a Novel Mechanism Involving Interleukin 4 Lymph Node Deviation and Interferon γ–mediated Splenic Anergy

Abstract: Induction of neonatal T cell tolerance to soluble antigens requires the use of incomplete Freund's adjuvant (IFA). The side effects that could be associated with IFA and the ill-defined mechanism underlying neonatal tolerance are setbacks for this otherwise attractive strategy for prevention of T cell–mediated autoimmune diseases. Presumably, IFA contributes a slow antigen release and induction of cytokines influential in T cell differentiation. Immunoglobulins (Igs) have long half-lives and could induce cytok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
83
0

Year Published

2000
2000
2006
2006

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(85 citation statements)
references
References 38 publications
(50 reference statements)
2
83
0
Order By: Relevance
“…Indeed, Zaghouani and coworkers (24) reported that tolerance induced by peptide IgG conjugates may be optimized by aggregation of the IgG and the induction of IL-10 synthesis by activated T cells. Although there are many differences between their system and ours (IgG2 vs IgG1 carrier; neonatal vs adult treatment; aggregated Ag is often immunogenic), the observation that IL-10 is a powerful suppressor to Th1 responses led us to test a possible role of this cytokine in gene-transferred tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Zaghouani and coworkers (24) reported that tolerance induced by peptide IgG conjugates may be optimized by aggregation of the IgG and the induction of IL-10 synthesis by activated T cells. Although there are many differences between their system and ours (IgG2 vs IgG1 carrier; neonatal vs adult treatment; aggregated Ag is often immunogenic), the observation that IL-10 is a powerful suppressor to Th1 responses led us to test a possible role of this cytokine in gene-transferred tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…First, although newborn mice are able to mount strong CTL responses (51-53), differentiation of type 2 cytokine-secreting T cells is preferentially induced by systemic Ag during the neonatal period (54,55). Several factors could contribute to this phenomenon: 1) differences in the function of APCs (56 -60); 2) lower frequency of T cells (61); 3) greater requirements for accessory cell factors (62); and 4) the high relative Ag dose (54).…”
Section: Discussionmentioning
confidence: 99%
“…IL-12 blocked/reversed UV radiation-induced immunosuppression (32)(33)(34), experimental autoimmune thyroiditis (35), neonatal tolerance in proteolipid protein-induced EAE (36) and in transplantation (37), and OVA-induced tolerance (38, 39), by promoting Th1 response and/or inhibiting Th2 polarization.…”
Section: Discussionmentioning
confidence: 99%